MyMobileSLT: mobile apps for student time management skills / Kamisah Ariffin, Nur Asmaliza Mohd Noor and Asmidar Alias - Ariffin, Kamisah; Mohd Noor, Nur Asmaliza; Alias, Asmidar (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
Empirical studies have reported that some university students had experienced problems in meeting their deadlines for given study tasks, indicating that they might be having poor time management. Thus, a tool that can guide students in time management, and act as a preventive measure to the problems of procrastination, disorganization, interruptions and workload pressure, is needed to help reduce the time management problem. This study proposes MyMobileSLT (Student Learning Time), a mobile application, which can help university students control their time for academic activities effectively. This application has been created to replace the previous MySLT which was the hard copy, conventional version of the present application. This paper examines users' perception on the perceived ease of use and perceived usefulness of this innovation. Using Davies' Technology Acceptance Model for predicting user acceptance and usage of new information systems, MyMobileSLT is evaluated based on the constructs of perceived ease of use and perceived usefulness. In general, users found MyMobileSLT easier to use and more practical compared to the conventional version. As MyMobileSLT offers methods and techniques to optimize efficiency in time management, users found it useful as a possible tool to be utilized for student time management.